Interference with RUNX1/ETO Leukemogenic Function by Cell-Penetrating Peptides Targeting the NHR2 Oligomerization Domain - Bartel, Yvonne (Hindawi Publishing Corporation, 2013)
The leukemia-associated fusion protein RUNX1/ETO is generated by the chromosomal translocation t(8;21) which appears in about 12% of all de novo acute myeloid leukemias (AMLs). Essential for the oncogenic potential of RUNX1/ETO is the oligomerization of the chimeric fusion protein through the nervy homology region 2 (NHR2) within ETO. In previous studies, we have shown that the intracellular expression of peptides containing the NHR2 domain inhibits RUNX1/ETO oligomerization, thereby preventing cell proliferation and inducing differentiation of RUNX1/ETO transformed cells. Here, we show that introduction of a recombinant TAT-NHR2 fusion polypeptide into the RUNX1/ETO growth-dependent myeloid cell line Kasumi-1 results in decreased cell proliferation and increased numbers of apoptotic cells. This effect was highly specific and mediated by binding the TAT-NHR2 peptide to ETO sequences, as TAT-polypeptides containing the oligomerization domain of BCR did not affect cell proliferation or apoptosis in Kasumi-1 cells. Thus, the selective interference with NHR2-mediated oligomerization by peptides represents a challenging but promising strategy for the inhibition of the leukemogenic potential of RUNX1/ETO in t(8;21)-positive leukemia.